APPLICATION OF THERAPY BRISK WALKING EXERCISE ELDERLY BLOOD PRESSURE WITH HYPERTENSION IN THE PUSKESMAS AMBARAWA - Samsuri Samsuri; Ns. Diana Dayaningsih (Lembaga Pengembangan Kinerja Dosen, 2021)
The elderly are the largest contributor to hypertension worldwide. Hypertension or an increased blood pressure > 140/90 mmHg. Brisk Walking Exercise therapy is a non-pharmacological therapy to control blood pressure. This case study aims to describe the application of Brisk Walking Exercise to reduce blood pressure in the elderly with hypertension. This research method uses a descriptive method involving 2 respondents with the criteria of elderly aged >6O years.category 1 hypertension.the results of this case study show a decrease in blood pressure between before and after brisk walking exercise therapy. Subject I experienced an average decrease of 3.71 mmHg in systolic and diastolic an average decrease of 1.71 mmHg.subject II experienced an average decrease of 4.41 mmHg in systolic blood pressure while in diastolic blood pressure there was an average decrease of 1.71 mmHg. Subject II experienced an average decrease of 4.14 mmHg in systolic and diastolic an average decrease of 3.14 mmHg.the conclusion of this case study is that brisk walking exercise therapy is effective in reducing blood pressure in both subjects.brisk walking exercise therapy is recommended as a nursing intervention in hypertension management in the elderly with hypertension.